UNESCO KNOWLEDGE SOCIETIES AND HADITH KNOWLEDGE SOCIETIES: Where Each Stands from the Other? - Alhasawi, Nourah (Journal of Dharma, 2019)
UNESCO has introduced its concept of knowledge societies to the world more than a decade ago. Knowledge Societies accept and support all forms knowledge including religious knowledge presumably. Due to their tendencies to be normative and have their own value systems, religious communities might have challenges in being part of Knowledge Societies as they are introduced by the UNESCO. The UNESCO, on the other hand, seems to have its own criteria by which it welcomes diversity. In this study, I introduce Hadith knowledge societies as a religious one. I explore the possibility of religious knowledge societies to accept and be accepted according to the UNESCO’s vision and characteristics of knowledge societies. This qualitative study thematically analyzes hadiths to point out the features of Hadith knowledge societies. The results of data analysis show that there are several common points between UNESCO and Hadith knowledge societies. Also, there are points considered by UNESCO crucial to its knowledge societies, while Hadith knowledge societies puts some restrictions on them and vice versa.